New Insights into Potocki-Shaffer Syndrome: Report of Two Novel Cases and Literature Review - Slavica Trajkova; Eleonora Di Gregorio; Giovanni Battista Ferrero; Diana Carli; Lisa Pavinato; Geoffroy Delplancq; Paul Kuentz; Alfredo Brusco (Brain Sciences, 2020)
Potocki-Shaffer syndrome (PSS) is a rare non-recurrent contiguous gene deletion syndrome involving chromosome 11p11.2. Current literature implies a minimal region with haploinsufficiency of three genes, ALX4 (parietal foramina), EXT2 (multiple exostoses), and PHF21A (craniofacial anomalies, and intellectual disability). The rest of the PSS phenotype is still not associated with a specific gene. We report a systematic review of the literature and included two novel cases. Because deletions are highly variable in size, we defined three groups of patients considering the PSS-genes involved. We found 23 full PSS cases (ALX4, EXT2, and PHF21A), 14 cases with EXT2-ALX4, and three with PHF21A only. Among the latter, we describe a novel male child showing developmental delay, café-au-lait spots, liner postnatal overgrowth and West-like epileptic encephalopathy. We suggest PSS cases may have epileptic spasms early in life, and PHF21A is likely to be the causative gene. Given their subtle presentation these may be overlooked and if left untreated could lead to a severe type or deterioration in the developmental plateau. If our hypothesis is correct, a timely therapy may ameliorate PSS phenotype and improve patients’ outcomes. Our analysis also shows PHF21A is a candidate for the overgrowth phenotype.